Pengaruh LMX dan teamwork terhadap kinerja karyawan di PT XYZ - Tan, Donny Sutanto; Susanto, Eko Harry (Universitas Tarumanagara, 2017)
An organization consists of many or several people. A leader is required to direct, instruct, be a place to ask questions, and be an example for subordinates. A leader is an essential element in an organization. According to LMX theory, a leader shows a more inclusive and communicative attitude toward certain members only. The LMX theory emphasizes the quality of relationships between leaders and members in the organization. Organization has a variety of processes that require the parties to work together to achieve goals. The company assigns working teams for higher effectiveness can be achieved by teamwork. Teamwork can improve employee performance and has a positive influence on all dimensions of employee performance. This research observes the employees−superiors interaction level, teamwork level, and performance based on LMX−teamwork variables. Using the quantitative method and Likert scale questionnaire unto 82 samples of 103 populations. The result shows that: [1] LMX concepts were applied in the company; [2] the lack of teamwork within the company; [3] the ability of LMX and teamwork to affect performance is 53.1%; [4] LMX’s coefficient value of 0.730 indicates a positive relationship between LMX and performance; teamwork’s coefficient value of -0.004 indicates a negative relationship toward performance; [5] LMX has a significant effect on performance; teamwork does not affect performance; LMX and teamwork altogether have a significant influence on performance.